2012
DOI: 10.1093/cercor/bhr224
|View full text |Cite
|
Sign up to set email alerts
|

Hyperconnectivity and Slow Synapses during Early Development of Medial Prefrontal Cortex in a Mouse Model for Mental Retardation and Autism

Abstract: Neuronal theories of neurodevelopmental disorders (NDDs) of autism and mental retardation propose that abnormal connectivity underlies deficits in attentional processing. We tested this theory by studying unitary synaptic connections between layer 5 pyramidal neurons within medial prefrontal cortex (mPFC) networks in the Fmr1-KO mouse model for mental retardation and autism. In line with predictions from neurocognitive theory, we found that neighboring pyramidal neurons were hyperconnected during a critical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 58 publications
8
70
1
3
Order By: Relevance
“…For example, input-specific synaptic plasticity in frontal cortex is impaired in neurodevelopmental disorders (62), and axonal organization and development in the prefrontal cortex are disrupted in autism (63). Hyperconnectivity and slow synaptic dynamics are observed in the mPFC of the Fmr1 −/− mouse, a model of fragile-X syndrome, autism, and mental retardation (64). Notably, this delay in synaptic maturation arises during the second to third postnatal week of development, largely coinciding with the critical period observed here for developing acoustic preference.…”
Section: Discussionmentioning
confidence: 99%
“…For example, input-specific synaptic plasticity in frontal cortex is impaired in neurodevelopmental disorders (62), and axonal organization and development in the prefrontal cortex are disrupted in autism (63). Hyperconnectivity and slow synaptic dynamics are observed in the mPFC of the Fmr1 −/− mouse, a model of fragile-X syndrome, autism, and mental retardation (64). Notably, this delay in synaptic maturation arises during the second to third postnatal week of development, largely coinciding with the critical period observed here for developing acoustic preference.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiple patch-clamp recordings of neighboring L5 cortical pyramidal neurons in acute slices of prefrontal cortex from Fmr1 KO mice, a recent study demonstrated that such clusters of neurons are hyperconnected (Fig. 4D) (Testa-Silva et al, 2012). Importantly, this defect was transient and occurred only during a critical period in mouse brain development (2 nd and 3 rd postnatal weeks), which may be particularly important for FXS pathogenesis, since it coincides with a time when Fmr1 KO mice exhibit a variety of other transient synaptic or brain circuit alterations (Bureau et al, 2008; Cruz-Martin et al, 2010; Goncalves et al, 2013; Harlow et al, 2010; He et al, 2014; Meredith et al, 2011).…”
Section: Local Circuits and Networkmentioning
confidence: 99%
“…A prominent neurobiological theory postulates that ASD is characterized by an E/I imbalance in local neural circuits that subserve sensory, social, and affective processes (105109). E/I imbalance in ASD is thought to alter local and global brain signaling and contribute to atypical fluctuations in regional fMRI signals (64, 110), leading to difficulties with modulating flexible and goal-directed behaviors.…”
Section: Neurophysiological Basis Of Dmn Dysfunction In Asdmentioning
confidence: 99%